Sartre's Thinking Of Marx - Lomak, Stephen Paul (My University, 1987)
Jean-Paul Sartre' s central purpose in writing the Critique of Dialectical Reason was to render intelligible Karl Marx's principle that circumstances make people just as much as people make circumstances. With the intent of complementing Marx's work, Sartre sought to theoretically connect the marxist outline of social process with its constituting parts--individuals. He sought to do this without ascribing to circumstances a superorganic existence, and in terms of the general structure of individual action per se. In place of a super organic being he attributed unintended consequences to all individual action (as well as intended consequences). The actual influence of circumstances upon people he explained by the fact that products bear some trace of the intentions of those who made them. The product becomes a sign, and people construct about them a world of signs.
Within this world of signs people tend to become separated as mediations between constructed things. It is in this sense, that is, in explaining how social relations tend to occur indirectly through the products of praxis, that Sartre sought to justify a rejection of organicism by developing his interpretation of Marx's theory of fetishism.
Keywords: Jean-Paul Sartre; Karl Marx; fetishism theory; Philosophy; Philosophy